Millennials’ travel motivations and desired activities within destinations: A comparative study of the US and the UK - Rita, P.; Brochado, A.; Dimova, L. (Current Issues in Tourism, 2019)
Millennials are one of the largest groups to be targeted by tourism companies. This paper compares the travel motivations of Millennials from both the United States and the United Kingdom by ratings, rankings and perceptual structures of both push and pull factors. This exploratory study used a questionnaire to examine the inner motivations (e.g. push factors) and preferred destination activities (e.g. pull factors) of American and British Millennials (n?=?322). Data analysis included the non-parametric Mann–Whitney U test, Kendall’s coefficient of concordance, an alternating least-squares algorithm (ALSCAL) model and ordinal regression. The results reveal that American and British Millennials are quite homogeneous in their push travel motivations and destination activity preferences. The most important motivational factors for both are ‘to relax’ and ‘to escape from the ordinary’. Both nationalities also agree that the most attractive destination activities are ‘to try local food’ and ‘to go sightseeing’. The findings indicate that the US and UK samples are similar and that there is room for segmentation according to demographics.